Zeitmasze (Time-Measures): For 5 wood-winds - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2008)
Dress rehearsal, introduction and concert of ZEITMASZE conducted by Stockhausen( Colour film by Suzanne Stephens ) ( Archive No. 27 / 1 )Dress rehearsal and performance of ZEITMASZE, Alte Oper Frankfurt, August 21st 1992with Ensemble Modern conducted by Karlheinz StockhausenLanguage: German, with written transcription of the introduction in English by Jayne Obst